Simulation and techno-economic evaluation of integrated palm oil mill processes for advancing a circular economy - Sulin, Siti Naderah; Mokhtar, Mohd Noriznan; Baharuddin, Azhari Samsu; Mohammed, Mohd Afandi P. (Elsevier, 2025)
The palm oil industry faces increasing pressure to adopt sustainable and circular production practices, particularly in waste management and greenhouse gas (GHG) emissions reduction. Integrated biomass utilization within palm oil mills (POMs) offers a promising approach to improve both environmental and economic outcomes. This study evaluates the techno-economic and environmental performance of an integrated POM system incorporating palm oil mill effluent (POME) treatment, empty fruit bunch (EFB) composting, and residual oil recovery within a unified flowsheet. A detailed simulation model of a 60 MT/h mill was developed using SuperPro Designer® software, based on actual mill operations and literature data. The model assessed mass and energy balances, capital and operating costs, and carbon dioxide (CO2) equivalent emissions. Results showed a 5 % increase in revenue through by-product valorization and a 53 % reduction in CO2 equivalent emissions when combining EFB composting with biogas capture. The system achieved a positive net present value (NPV) of MYR 75.63 million, an internal rate of return (IRR) of 30.08 %, a return on investment (ROI) of 19.20 %, and a payback period (PBP) of 5.21 years. Sensitivity analysis showed that the prices of fresh fruit bunches (FFB), crude palm oil (CPO), and the CPO yield are key factors influencing economic performance. These outcomes highlight the feasibility of implementing circular economy principles, where waste streams are transformed into valuable products such as compost, biogas, and recovered oil, thereby closing material loops and reducing environmental impact.